Digital health solutions for improving healthcare accessibility in Jordanian communities: A literature review - Ashour, Abdallah; Hani, Salam Bani; Eyadat, Anwar; Al-Bsheish, Mohammad; Alsyouf, Adi (Edelweiss Applied Science and Technology, 2025)
With the rapid advancement of technology, digital health tools such as telemedicine, mobile health applications, and electronic health records have emerged as innovative approaches to address healthcare disparities. This review aims to examine the current state of digital health implementation in Jordan, highlighting its impact on underserved populations, particularly in rural and remote areas. The search was conducted utilizing several electronic databases including CINAHL, Google Scholar, ResearchGate, and ScienceDirect. A total of 620 articles were retrieved. After duplicate removal, 540 articles were screened for titles and abstracts. 120 relevant articles underwent full-text screening, of which 75 were found eligible to be included in the review. Key challenges, including technological infrastructure, digital literacy, and regulatory frameworks, are discussed alongside opportunities for improvement. Findings suggest that integrating digital health solutions can significantly enhance healthcare accessibility, reduce costs, and improve health outcomes. The review emphasizes the need for collaboration among policymakers, healthcare providers, and technology developers to overcome barriers and ensure equitable access to digital health services. This study contributes to the growing body of knowledge about leveraging technology to address healthcare challenges in Jordan and offers recommendations for future research and policy development.